“Who was Ernestina de Champourcin!”: Contribution of the poetess to the Lyceum Women’s Club (1926-1936) - Esteban Cerezo, M. Dolores (Hispania Nova, 2024)
This study aims to analyze the role of Ernestina de Champourcin at the Lyceum Club Femenino in Madrid during the years 1926-1936. Her contribution focused on collaborating as the secretary of the institution, organizing conferences, and literary activities. This article aims to fill a gap in current historiography regarding this poet’s specific contribution to the Lyceum Club. To achieve this goal, I have supported the research using the Archive of the Residencia de Señoritas, the poet’s own letters (some unpublished and others published) deposited in the Ernestina de Champourcin Personal Fund of the General Archive of the University of Navarra, contrasted with her appearances in the press and in the correspondence of her contemporaries. Additionally, to highlight specific references, the unpublished Family Archive and the Documentary Center of Historical Memory have been consulted.